Konferencje i szkolenia online zorganizowane w Polsce w czasie pandemii COVID-19 – wybór (od listopada 2021 do marca 2022 roku) - Kowalska, Marzena (Acta Universitatis Lodziensis. Folia Librorum, 2022)
Selective list of conferences and trainings in the field of information and book science, as well as social communication and media, which were held online in Poland during the COVID-19 pandemic from November 2021 to March 2022. National and international events have been registered.